Optimization of Recreational Park Development in Klaten District by Using Critical Path Method (CPM) - Fitriana Wulandari (International Journal of Economics, Business Management and Accounting (IJEBMA), 2022)
Recreation Parks are one of the tourist/visit destinations for people to fill their free time or vacation. The plan to build a recreation park in Klaten Regency is expected to be completed within 70 days. By preparing good project management, it is possible to estimate the time and costs required to carry out the project, so that the project can be completed within the desired time with minimum total costs. The method used to solve this problem is the optimization of the critical path method. The critical path method is a method used to determine the sequence of critical activities or activities that cannot be postponed along with the fastest total time to complete the entire project. The results of the discussion using the Critical Path Method regarding the problem of building a Recreational Park project in Klaten Regency showed that the fastest time to complete the project was 84 days at a cost of Rp. 540,000,000,- and after optimization according to the expected time (70 days), the costs that must be incurred are Rp. 566,750,000